2 Exposure to violence: a latent profile analysis: victimisation, observation, and family conflict in a young inner-city disadvantaged sample. (19th September 2017) - Roehler, Douglas; Stoddard, Sarah; Heinze, Justin; Bauermeister, Jose; Zimmerman, Marc
Abstract : Statement of purpose: Exposure to Violence (ETV) is the most frequently reported stressor in the lives of African American youth. Although ETV is associated with many later detrimental health effects, previous measures of ETV do not consider the fact that many individuals are exposed to multiple forms of violence concurrently. Studies that simply sum multiple forms of ETV fail to differentiate individuals who are experiencing unique ETV profiles, potentially masking important nuances in the ways youth experience violence. The objective of this study is to identify different profiles of ETV and examine how these different profiles differ by demographic characteristics (e.g., sex, ethnicity) and violence perpetration. Methods: Participants included 770 youth (M=17.9 years; 80% Black or African American; 48% male) from a disadvantaged community. Youth were asked to measure their levels of family conflict, amount of violence they have observed, and violent victimisation. Multiple latent profile analyses were performed to find classes with the best fit. Groups were then compared using ANOVAs and chi-squares to determine differences in demographics and violence perpetration. Results: A latent profile analysis indicated that a three-group solution provided the best fit (low ETV, medium ETV, high ETV). Post hoc analyses indicated that males were more likely to be in the high ETV group, and a positive relationship between ETV and violence perpetration. Conclusions: These findings indicate three clear profiles and these individual profiles were associated important risk factors. Significance and Contributions to Violence Prevention Science: Researchers can begin studying ETV and the subsequent outcomes in a more nuanced way. Such patterning of different forms of ETV may allow health practitioners to better identify and address different forms of ETV, allowing health care providers to be less likely to miss identifying ETV, which will increase the chances that the victim receives adequate treatment.